Practices of obstetric semiology in a medical skills laboratory: an experience report - Feitosa, Ana Beatriz da Silva (2024)
General practitioners are responsible for prenatal consults and other healthcare services for pregnant women. Thus, they need to have an efficient academic background in Obstetrics. This experience report aimed to describe practices in obstetric semiology occurring between March and November 2023 in a medical skills laboratory of a higher education institution in Pernambuco. The students practiced semiology techniques used in Obstetrics and the care of pregnant women with pathologies. The activities supplied the demands of the health of women and validated the urgency of a medical formation centered on direct knowledge application, improving its efficiency and giving students a leading role.